2020
DOI: 10.14295/transportes.v28i2.1909
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of steel slag in micro surfacing

Abstract: Micro surfacing (MS) is a type of bituminous coating frequently applied in the surface of pavement structures in order to prevent the occurrence of common distress and/or as a maintenance procedure. Micro surfacing has successfully been used in some states of Brazil as well as in many countries all over the world. Local aggregates used for micro surfacing composition are in some cases scarce and/or expensive. Therefore, the main objective of the present research is to verify the technical, financial and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Nascimento et al 19 tested the adhesion between MS and the original pavement at different temperatures from the point of view of interlayer bonding and concluded that MS are more susceptible to damage in high temperature areas. LWT and WTAT have also been applied as indicators of skid and abrasion resistance to investigate the effects of various factors, such as water content, 20 snowmelt, 21 steel slag, 22 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Nascimento et al 19 tested the adhesion between MS and the original pavement at different temperatures from the point of view of interlayer bonding and concluded that MS are more susceptible to damage in high temperature areas. LWT and WTAT have also been applied as indicators of skid and abrasion resistance to investigate the effects of various factors, such as water content, 20 snowmelt, 21 steel slag, 22 and so forth.…”
Section: Introductionmentioning
confidence: 99%